Le tournant managérial dans le secteur public européen : quelles conséquences sur l’action publique ? - Christophe Nosbonne (La Nouvelle Revue du Travail, 2013)
The article highlights transformations in public action by examining the consequences of the managerial turn that the public sector has taken since the 1980s within a European context. Starting with divergences in the approaches deemed coherent to each country's public service and public employment policies, the impact of European construction on national contexts will be analysed in conjunction with programmes reforming the State and its administrations. The focus here will be on a common benchmark entitled new public management, featuring its own principles, values and objectives. The assumption is that public action requires a substantial re-definition, and that this is achieved by means of a dual segmentation of the activities and jobs found at the heart of public action's centrifugal process.